Admission to Hospital with Childhood Acute Gastroenteritis in Kuala Lumpur, Malaysia - Izzuddin, P.W.; Lee, W.S. (2007)
Mortality from acute diarrhoea in developed countries is low, but the morbidity and financial cost remains significant. A one-year prospective, descriptive, non-interventional, hospital-based study of acute gastroenteritis (AGE) was conducted in the year 2002 in the paediatric unit of University of Malaya Medical Centre, Kuala Lumpur, an urban hospital in Malaysia to determine its morbidity and management. During the study period, 393 children with AGE were admitted, utilizing 0.50% of total patient-bed-day of the hospital. The median duration of symptoms before admission was two days. Seventy-seven percent of patients had consulted family physicians before admission. Anti-diarrhoeal drugs (57%) and anti-emetics (48%) were commonly prescribed but oral rehydrating solution (36%) was rarely advised. Upon admission, severe vomiting (24%) and severe diarrhea (24%) were not common, while 17% had moderate or severe dehydration. Rotavirus (22%) was the commonest pathogen identified. Electrolyte derangement, secondary septicaemia and chronic diarrhoea were all rare. Eighty-nine percent of patients received intravenous fluid therapy whilst in the hospital. No death was noted. The morbidity and mortality of children with AGE requiring hospital care in this study was low. However, preadmission management and fluid therapy after admission was not ideal. Efforts to courage better adherence to established management protocol of AGE among family physicians and hospital clinicians should be instituted.